MANAGEMENT’S PERCEPTIONS TOWARDS THE VISION AND MISSION IN SECONDARY EDUCATION SCHOOLS IN NORTH CYPRUS - Ertuğruloğlu, Oya (International Online Journal of Education and Teaching, 2024)
The basis of effective management requires that the objectives be clearly stated and determined correctly. From an organizational perspective, goals form the basis of the activities of organizations and therefore their existence. While the framework determined by national education systems gains importance in determining the vision and mission studies of schools, the structure of administrators and school organizations, the goals they set, and strategic plans gain importance in the implementation phase. The purpose of this research is to reveal the vision and mission perceptions of administrators working in secondary schools in Northern Cyprus. The research was designed using a case study, one of the qualitative research methods, involving 20 school administrators working in public and private schools across different regions. The data obtained within the scope of the research were analyzed using content analysis, resulting in the identification of 2 main themes and 5 sub-themes. Within the framework of the anecdotes and codes obtained within the scope of these themes, the findings regarding the vision and mission perception of school administrators were accessed, shedding light on the process of planning and implementing goals and strategies.